In vitro activities of rifapentine and rifampin, alone and in combination with six other antibiotics, against methicillin-susceptible and methicillin-resistant staphylococci of different species. - Varaldo, P E (1985)
The antistaphylococcal activity of rifapentine, a new rifamycin SV derivative, was evaluated in vitro and compared with that of rifampin. A total of 313 staphylococcal strains freshly isolated from clinical material and including representatives of all currently recognized Staphylococcus species of human origin were used. The susceptibility to methicillin of all the test strains was determined preliminarily. Despite minor differences with some species, the MICs of rifapentine were found to be substantially similar to those of rifampin. Methicillin-resistant strains of all species were most resistant to rifapentine and rifampin than were their methicillin-susceptible counterparts. For most strains tested, the MBCs of both rifamycins exceeded by twofold the respective MICs. Both the checkerboard dilution and time-kill methods were used to determine the interactions of rifapentine or rifampin with six different antibiotics: cefamandole, vancomycin, teicoplanin, gentamicin, erythromycin, and fusidic acid. No significant differences between the two rifamycins in the combinations were observed against either methicillin-susceptible or methicillin-resistant strains. Minor differences were noted depending on the second antibiotic tested or the staphylococcal species examined. Antagonism was never observed, and indifference was the prevalent response. Cases of synergism were observed occasionally with the checkerboard method and slightly more often with the time-kill method.